Biopiracy' and Patents - Developing Countries' fears are exaggerated - Bastuck, Christian (Department of Commercial Law, 2014)
This thesis will examine such ''biopiracy' patents' and tries to evaluate whether the criticisms related with them are true and whether and how far these patents have indeed negative impacts on indigenous communities and developing countries. It will be shown that the fear of the slogan 'biopiracy' is exaggerated since the criticisms related with it are largely unjustified and since there is no direct impact on indigenous communities or developing countries. Even the few negative impacts can be resolved by the developing countries with the help of suitable national legislation. Thus, developing countries should rather enact appropriate legislation to make use of the available TRIPS regulations to promote innovation in their own territory to benefit better from their resources than it is the case up to now. [...]